2021
DOI: 10.3389/fimmu.2021.676686
|View full text |Cite
|
Sign up to set email alerts
|

Memory B Cells in Multiple Sclerosis: Emerging Players in Disease Pathogenesis

Abstract: Multiple Sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system. Once thought to be primarily driven by T cells, B cells are emerging as central players in MS immunopathogenesis. Interest in multiple B cell phenotypes in MS expanded following the efficacy of B cell-depleting agents targeting CD20 in relapsing-remitting MS and inflammatory primary progressive MS patients. Interestingly, these therapies primarily target non-antibody secreting cells. Emerging studies seek to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 208 publications
(239 reference statements)
0
22
0
Order By: Relevance
“…This suggests that antibody-independent functions of B cells are likely also important in MS, including antigen presentation to CD4 + T cells and/or induction of “auto proliferative” Th1 CD4 + T cells ( 6 ), possibly facilitated by the HLA-DR15 gene variant ( 7 ). While uncertainty remains about which MBC subpopulations and functions might mediate these effects ( 8 ), one population that has emerged as being of particular interest is MBCs expressing the T-box family transcription factor (T-bet), the activity of which results in Th1-skewed immune responses and enhances control of infections by viruses and other intracellular pathogens ( 9 , 10 ). Early reports highlighted that some MS patients exhibit an expansion of “age-associated B cells” including double negative (IgD - /CD27 - ) B cells as well as CD21 low B cells ( 11 ), which are now recognised to be primarily T-bet + MBCs ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that antibody-independent functions of B cells are likely also important in MS, including antigen presentation to CD4 + T cells and/or induction of “auto proliferative” Th1 CD4 + T cells ( 6 ), possibly facilitated by the HLA-DR15 gene variant ( 7 ). While uncertainty remains about which MBC subpopulations and functions might mediate these effects ( 8 ), one population that has emerged as being of particular interest is MBCs expressing the T-box family transcription factor (T-bet), the activity of which results in Th1-skewed immune responses and enhances control of infections by viruses and other intracellular pathogens ( 9 , 10 ). Early reports highlighted that some MS patients exhibit an expansion of “age-associated B cells” including double negative (IgD - /CD27 - ) B cells as well as CD21 low B cells ( 11 ), which are now recognised to be primarily T-bet + MBCs ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been shown that memory B cells can function as potent antigen presenting cells (APCs) ( 50 ) with proinflammatory tendencies including their capacity to express high levels of proinflammatory cytokines including GM-CSF, TNF-α and lymphotoxin ( 51 ). Class-switched memory B cells not only populate the cerebrospinal fluid (CSF) of MS patients ( 52 ) but are also found within the brain parenchyma ( 53 ) with studies demonstrating that the increased accumulation of class-switched memory B cells in the CSF also correlates with the intrathecal synthesis of IgG ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The example of tabalumab illustrates the complex nature of B cell involvement in MS and emphasizes the important role of Bmem in MS immunopathology [ 73 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical study on tabalumab illustrates the complex nature of B cell actions and effects on the autoimmune system [ 69 ] and highlights the importance of memory B cells (Bmem) as central players in the MS immunopathogenesis [ 73 , 78 , 79 ]. Bmem display diverse effector functions including cytokine production, antigen presentation, and serving as antigen-experienced precursors to antibody-secreting cells [ 78 ].…”
Section: Failed Mabs In Relapsing Multiple Sclerosismentioning
confidence: 99%